(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Alcoholic neuropathy occurs due to damage to the nerves that results from excessive intake of alcohol. Alcoholic neuropathy’s precise cause is uncertain. It probably involves both the direct alcohol poisoning of the nerve and the consequences of poor nutrition linked to alcoholism. A 33- year-old single male patient visited Panchakarma OPD with weakness, numbness and pricking pain of both lower and upper limbs. Onset was gradual, started as numbness of both feet followed by difficulty in walking. Later it affects both lower and upper limbs along with pins and needle sensation and he was unable to walk without support. He also had difficulty to hold or grip objects. Along with that he had burning sensation over both feet and hyperesthesia especially over both feet and hand. At times, the agony was so intense that it prevented him from touching his body. For the previous four to five years, the patient has been a regular and heavy drinker with poor eating habits. Initially consulted an allopathic doctor for the same. Medications were given. The patient got admitted to IPD, Panchakarma, Govt. Ayurveda College Hospital. The clinical presentation closely resembles that of Sarvanga vata with Madya and Vishama bhojana (irregular eating habits) as Nidana. The treatment plan was designed in accordance with Vatavyadhi and Madatyaya Chikitsa. The patient got relief in the above said symptoms with Ayurveda therapies with in a period of 40 days. The potential of Ayurveda to alleviate the symptoms of alcohol-induced polyneuropathy has been explored in this case study. The case highlights the importance of stage-wise selection of drugs and external therapies as per the pathogenesis of the disease.